Negotiating Implicit Meaning on the Internet: A Case Study - Ferrucci, Francesca (International Journal of Linguistics, 2023)
Negotiating the meaning of words and sentences is a fundamental part of verbal interactions. This essay aims to examine a particular type of negotiation, that relating to the content of presuppositions, which are placed, together with the implicatures, in the phenomena of implicit communication. The research made use of automatic tools for querying empirical data: a database of lexical presupposition triggers for the Italian language, including approximately 20,000 entries (simple lexemes and multiword expressions) and the corpus of Computer Mediated Communication Web2Corpus_it, specifically in its public chat sections, which contains about 300,000 tokens. Quantitative data are provided in relation to the pragmatic function of negotiation, its initiation stage, and the types of presupposition triggers involved. In the context of the media characteristics of chats, which must be considered to discuss the results, the items of implicit meaning negotiation provide corpus-based evidence of the conditions under which presuppositions are available to the receiver’s monitoring of the meaning and consequent possible reaction.